Development of quantum learning modules in science learning materials for animal and human movement organs toeincrease interest and learning outcomes of fifth grade elementary school students - Nugroho, Utut Febriaryanto (ARKA INSTITUTE, 2022)
This study aims to describe the procedure for developings Quantum Learnings modules, to produce appropriate Quantum Learning module products, and to produce effective Quantum Learning module products to increase students' interest in learning and learning outcomes. This research uses research and development procedures. Research and development with the ADDIE model. The methods of collecting data are questionnaires, tests, and interviews. Testing the questionnaire instrument using validity and reliability tests. The test instrument was tested with validity, reliability, discriminatory test, and level of difficulty. The questionnaire instrument for learning interest from 36 items tested was valid and reliable, there were 30 items. Data analysis techniques include product data analysis, initial data analysis, and final data analysis (differentiation test). The results showed that the Quantum Learning Science module that had been developed met the eligibility criteria, in this case it reached the validity of both material experts and media experts of 85.6% > 70%. The science module product with the Quantum Learning (QL) approach that was developed shows its effectiveness in increasing interest in learning and learning outcomes.